Pengaruh Model Pembelajaran Scientific Inquiry Terhadap Keterampilan Generik Sains Siswa - Putrini R Harahap, Saima; Aida, Nur; Muttaqin, Khairul (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2022)
This research aims to analyze the effect of the scientific inquiry learning model on students' generic science skills. This research is a quasi-experimental study with a two group pre-test-posttest design. The research population is all students of class X SMA Negeri 1 Percut Sei Tuan in the second semester of the 2016/2017 academic year. The sample in this study is taken by cluster random class, that is as many as 2 classes totaling 62 people. Class X MIA3 as an experimental class taught with the scientific inquiry learning model consisted of 30 students, class X MIA1 as a control class taught with conventional learning consisted of 32 students. This research instrument uses a generic science skill essay test consisting of 10 validated questions. The average value of students who are taught using the scientific inquiry learning model is 79.63 and for conventional learning it is 66.69. The results of the t-test obtained tcount = 5.729 and ttable = 1.669 so that tcount > ttable then Ha is accepted. The results showed that the scientific inquiry learning model had an effect on students' generic science skills